Work Life Balance (WLB) Complexity and Performance of Employees during Covid-19 Pandemic - Honorata Ratnawati Dwi Putranti; Suparmi Suparmi; Arianda Susilo (Arthatama: Journal of Business Management and Accounting, 2020)
Covid-19 pandemic that hit the world caused changes in all areas of the fabric of people's lives. Perceived changes, one of which is in the world of work, are causing changes in order and rules in the field of human resource management. This study aims to create a Work Live Balance (WLB) and flexible work model of employees in the 19th era. This study uses descriptive qualitative methods with the help of questionnaires and interviews. Resource persons are employees who are in Indonesia for all sectors. This study uses primary data of 200 people, from various companies throughout Indonesia by random sampling. Men and women in dividing time have different patterns. The more women get older the more they can divide their time between work and social life. Men have a more dynamic graph. Some types of work and some positions can arrange time from home, but there are types of work that must be done in person. The results of this study can provide input to companies in making decisions to welcome new normal, in the field of Human Resources management policies.